Model of Developing Oral Skills for Non-Arabic Learners at the University Level - Uril Bahruddin; Syuhadak Syuhadak; Sutaman Sutaman (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
Most of the Arabic language teaching institutions face difficulties in getting students to speak Arabic with them. However, there is an institution that is classified as successful in teaching speaking skills to its students. This study aims to describe the strategies used by the Ar-Rayah College of Languages (STIBA) in Sukabumi in teaching spoken Arabic to students and their impact on the development of speaking skills. This research uses a qualitative approach with a type of case study. The results of this study indicate that there is a set of strategies that contribute to the achievement of the Arabic language learning process at STIBA Ar-Rayah, including the appropriate Arabic language teaching curriculum, student placement in dormitories, long study time, adequate extra activities, giving additional lessons for the less fortunate, and the existence of native speaking lecturers. The strategy used has an impact on the development of students' speaking skills, where they can speak Arabic fluently in about 6 months, students use Arabic fluently every day, and the Arabic language used is Standard Arabic. The conclusion of this study is that the success of learning Arabic for non-Arabic speakers is supported by the existence of an appropriate strategy in addition to the success in functioning other learning elements.